Surface morphology and facets evolution of CeO2 nanoarray superstructures fabricated by pulsed laser deposition. (November 2016) - Wang, BinBin; Liu, LinFei; Wu, Xiang; Li, Qiang; Yao, YanJie; Lu, SaiDan; Li, YiJie
Abstract: Cerium oxide (CeO2 ) films with a series of nanoarray superstructures were prepared via pulse laser deposition (PLD). The facets transition from (001) to (111) and (110) was found in these samples, and the growth mechanism was proposed. The facets transition could be the result of nanostructure evolution which arises from the competition between formation energy and migration energy. The room temperature photoluminescence (RTPL) and UV–visible absorption spectrum revealed that these CeO2 nanoarray films have high content of oxygen defects and absorbance by turning nanostructures, which may contribute to their application. Graphical abstract: